The Strategic Dimension of the Dynamic Capabilities of Enterprises = Strategiczny wymiar dynamicznych zdolności przedsiębiorstw - Krzakiewicz, Kazimierz; Cyfert, Szymon (Zielona Góra: Faculty of Economics and Management Press)
The aim of this paper is to contribute to the debate on the concept of dynamic capabilities of enterprises and present of its principles from the perspective of strategic management. The paper starts with the presentation of importance of paradigms in strategic management. It is followed by the discussion of the concept of dynamic capabilities and of the strategic aspects of the concept of dynamic capabilities of enterprises.
Keywords: przedsiębiorstwo; zdolności dynamiczne; Zarządzanie strategiczne; enterprises; dynamic capabilities; Strategic management